"Even if someone has a physical disability, they can still participate": Youth with physical disabilities' motivational physical activity message preferences. Issue 1 (January 2020) - Larocca, Victoria; Fraser-Thomas, Jessica; Bassett-Gunter, Rebecca
Abstract: Background: Youth with disabilities (YWD) experience unique physical activity (PA) needs and subsequently experience low levels of PA and are vulnerable to the risks associated with physical inactivity. Persuasive PA messages have been shown to motivate able-bodied youth to engage in PA, but there is no known research examining the PA motivational messaging needs preferences of YWD. Objective: The objective of this study was to examine and understand the PA motivational messaging needs and preferences of YWD. Methods: Sixty YWD were randomized to view three PA messages: a) no youth, b) non-inclusive, and c) targeted. After viewing the PA messages, participants completed a survey which consisted of three open-ended questions probing participants about their PA messaging needs and preferences. Responses were analyzed using a qualitative approach through an interpretivist lens. Results: Two main themes emerged from the data: (1) factors that facilitate motivation for PA, with subthemes of reliability, happiness/hope, disability does not limit PA, thinking deeply, motivational, inclusivity, accessible information, and success stories; and (2) factors that negatively influence motivation for PA, with subthemes of sad and negative feelings, jealousy, not relatable, and reinforced physical limitations. Conclusions: An improved understanding of the messaging needs and preferences of YWD can inform the development of optimally effective targeted messages to promote and motivate PA among YWD. The results of this study can be useful for PA organizations in order to develop inclusive PA messages for YWD.